Analisis spasial persebaran dan faktor risiko tuberkulosis paru di wilayah kerja Puskesmas Hutabaginda Kecamatan Tarutung Kabupaten Tapanuli Utara tahun 2022 - Sitompul, Indah Sari; Ashar, Taufik (TROPHICO: Tropical Public Health J., 2024)
Pulmonary tuberculosis is one of the top 10 diseases that need to be addressed and is one of the most common diseases that cause death. Tarutung Subdistrict with Hutabaginda Health Center is the subdistrict with the highest cases of pulmonary tuberculosis in North Tapanuli Regency. The number of cases of pulmonary tuberculosis patients in 2022 was obtained as many as 59 cases, of which 40 cases with complete and traceable addresses. This research is a descriptive analysis research using quantitative research method with Cross Sectional research design. This study analyzed the distribution mapping and risk factors for the incidence of pulmonary tuberculosis in the Working Area of Puskesmas Hutabaginda, Tarutung Subdistrict, North Tapanuli Regency with a total sampling technique with a sample size of 40 people. Data were collected directly by the researcher through observation and interview with a research questionnaire. Data analysis showed that the majority of research respondents were male (70%), productive age (77.5%), with low education level (80%), still working (52.5%), not consuming alcohol (52.5%), not smoking (55%), no history of diabetes (62.5%), unqualified residential density (80%), unqualified house temperature (70%), unqualified house ventilation (77.5%), unqualified house humidity (97.5%), qualified wall type (60%), qualified floor type (57.5%), and qualified house lighting (62.5%). It is recommended that patients with pulmonary tuberculosis be able to maintain the health of the housing environment, and the Puskesmas is expected to be able to increase the promotion of clean and healthy living behaviors (PHBS) through socialization and counseling.